DERIVASI PRINSIP KONSEPTUAL TEORI PENDIDIKAN ISLAM - Rohiman Rohiman (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
Islamic education has principles in the development of theories. This principle leads to the formation of the concept of description in various components of education. The philosophical foundation in this principle becomes an important instrument in relating the philosophical side with the empirical in the context of the educational science of the Islamic perspective. Some of the main principles in Islamic education as basic assumptions in the embodiment of the theory developed. The link between humanity becomes an important point in the derivation of concepts derived for the implementation of education. The research method used by the author is Library Research, which is research that seeks to collect research data from existing literature. From the results of the author's search, there are several basic conceptions in Islamic education including the principle of understanding traditions and culture critically, education and development (the principle of change), openness to external information, perfection of knowledge and faith, necessity to teach, sincerity, continuity of learning, limited reason, and friendship between teachers and students. In this connection, these principles are used as a foundation within the framework of the development of Islamic education both theoretical and practical. These principles can be elaborated on the curriculum and methodology of Islamic education.